2018
DOI: 10.1159/000494670
|View full text |Cite
|
Sign up to set email alerts
|

Decremental Responses to Repetitive Nerve Stimulation in Amyotrophic Lateral Sclerosis

Abstract: Introduction: To illuminate the mechanism of neuromuscular junction involvement by analyzing the features of a slow-rate repetitive nerve simulation (RNS) and EMG in amyotrophic lateral sclerosis (ALS) patients. Methods: We retrospectively analyzed relationship between clinical features and the decremental response in RNS in 184 sporadic ALS patients. Results: (1) 44.3 and 43.5% of compound muscle action potentials (CMAP) decrement were more than –10% in deltoid muscle (Del) and Trap; (2) ALS patients were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…Moreover, this study showed that the onset of ALS did not affect the RNS decrement responses, which was consistent with previous research (8,18). However, some studies have shown that patients with upper limb onset had higher decremental percentages compared with those with other sites of onset (7,17). The underlying reason for these differences is unclear.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Moreover, this study showed that the onset of ALS did not affect the RNS decrement responses, which was consistent with previous research (8,18). However, some studies have shown that patients with upper limb onset had higher decremental percentages compared with those with other sites of onset (7,17). The underlying reason for these differences is unclear.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, more than 10% of the patients had a decrement of ≥20%. Although it has also been reported previously that the decremental percentage can reach 20% (4,7,8), the proportion of patients with such a characteristic was not mentioned. If the current electrophysiological diagnostic criteria were applied, more than 10% of ALS patients would be misdiagnosed.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations